Unpacking the "Black Box": Understanding the Effect of Social Network Characteristics on Safety Behaviors of Construction Workers. (18th November 2020) - Li, Shuquan; Yang, Pei; Wu, Xiuyu; Wang, Ge; Fan, Meng
Abstract : How to improve the safety behaviors of construction workers has dogged the realm of construction project management. Previous studies mainly focused on the individual and/or organizational factors shaping safety behaviors, while there is a dearth of research focusing on the effect of individual-organizational nexus (i.e., the network embeddedness of individuals within the organization). Thus, this study employs social network analysis (SNA) and multivariable regression analyses to explore the relationship between the characteristics of social networks of construction workers (i.e., degree, closeness, and betweenness centralities) and their safety behaviors (i.e., safety participation and safety compliance), considering the mediating role of safety communication. The primary data were collected from ten Chinese construction projects. The results include the following three aspects. First, degree centrality, closeness centrality, and betweenness centrality all exert significant positive effects on safety participation. Closeness centrality yields a positive effect on safety compliance in formal networks. Degree centrality has a positive effect on both safety compliance and safety participation, whereas the other two centrality characteristics exhibit no significant effect in informal networks. Second, in formal networks, safety communication plays a partial mediation role between closeness centrality and safety compliance and a full mediation role between degree and closeness centralities and safety participation. Third, in informal networks, safety communication plays a full mediation role between degree centrality and safety compliance and a partial mediation role between degree centrality and safety participation. This study provides new insights for construction project management in achieving improved safety performance via shaping the social network characteristics.